Penilaian Tingkat Kesehatan Koperasi Syariah Berdasarkan Peraturan Kementerian Koperasi Dan Ukm - Prayogo P Harto; Umi Amaliah; Sri Mulyati (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2018)
This study aims to determine the level of health of Sharia Multipurpose Cooperative X in Depok City based on the standards of The Cooperative Minister Regulation Number: 07/Per/Dep. 6/ IV/2016 concerning Health Assessment Guidelines for Sharia Cooperative. Assessment health level of cooperatives based on 8 aspects: aspects of capital, quality, management, efficiency, liquidity, independence and growth, cooperative identity, and promises to sharia principles. The results showed that the health level of Syariah Cooperative X in 2017 obtained a score of 61.99 categorized in Supervision.